PENGARUH KOMUNIKASI WORD OF MOUTH, KUALITAS PELAYANAN, KEPERCAYAAN KONSUMEN DAN CITRA MEREK TERHADAP LOYALITAS PELANGGAN DIMEDIASI KEPUASAN PELANGGAN UMKM KERUPUK TEMPE PADA UD DUA PUTRA DESA MENONGO KECAMATAN SUKODADI (ANALISIS METODE PARTIAL LEAST SQUAR - Husen; Muhtarom, Abid; Cholidah, Lilik Nur; Priambodo, Wisnu; Ningseh, Dewi Wulan Agustin (Program Studi Manajemen STIE Kesuma Negara Blitar, 2022)
This study aims to examine the effect of Word of Mouth communication, service quality, consumer trust and brand image on customer loyalty mediated by customer satisfaction of Tempe crackers at UD Two sons of Menongo Village, Sukodadi District. This research uses quantitative methods with SEM analysis through the Smart-PLS version 3.0 application. The tests carried out are the measurement model (Outer Model), structural model (Inner Model), mediation test and hypothesis testing. The research sample was 166 respondents. Based on the results of the study, it was obtained partially that the word of mouth communication relationship had a positive and significant effect on customer loyalty and customer satisfaction, service quality had a positive and significant effect on customer loyalty and customer satisfaction, consumer trust has a positive and significant effect on customer loyalty and customer satisfaction and brand image has a positive and significant effect on customer loyalty and customer satisfaction. The results of the mediation test partially show that Word of Mouth communication, service quality and consumer trust have a positive and insignificant effect on customer loyalty mediated by customer satisfaction said to be Non Mediation. Brand image has a positive and significant effect on customer loyalty mediated by customer satisfaction, which is called Partial Mediation. Service quality and consumer trust have no significant positive effect on customer loyalty mediated by non-mediation. Brand image has a positive and significant effect on customer loyalty mediated by customer satisfaction, which is called Partial Mediation. Service quality and consumer trust have no significant positive effect on customer loyalty mediated by non-mediation. Brand image has a positive and significant effect on customer loyalty mediated by customer satisfaction, which is called Partial Mediation. Keywords: Word of Mouth Communication, Service Quality, Consumer Trust, Brand Image, Customer Loyalty and Customer Satisfaction